Compatibilism, indeterminism, and chance - Mackie, Penelope (Cambridge University Press, 2018)
Many contemporary compatibilists about free will and determinism are agnostic about whether determinism is true, yet do not doubt that we have free will. They are thus committed to the thesis that free will is compatible with both determinism and indeterminism. This paper explores the prospects for this version of compatibilism, including its response to the argument (traditionally employed against incompatibilist accounts of free will) that indeterminism would introduce an element of randomness or chance or luck that is inimical to free will and moral responsibility.